MRI manifestations and quantitative parameters of fat pad PDW-SPAIR in patients with knee osteoarthritis and their predictive value - He, Yanan; Huang, Yaoqu; Chen, Chuying; Yi, Lilei; Zhou, Shouguo; Wang, Juan (Technology and health care, 2025)
BackgroundKnee osteoarthritis (KOA) is a degenerative joint disease characterized by the breakdown of cartilage and underlying bone, often leading to pain and stiffness. There is limited research on the correlation between magnetic resonance imaging (MRI) manifestations and changes in quantitative parameters of the proton density-weighted spectral attenuated inversion recovery (PDW-SPAIR) sequence in the fat pad of KOA patients.ObjectiveTo investigate the MRI manifestations and quantitative parameters of fat pad PDW-SPAIR in patients with KOA and their predictive value.Methods82 patients with KOA admitted to the hospital from January 2023 to January 2024 were selected as the study subjects. All of them received an MRI examination before the operation. Their MRI manifestations and quantitative parameters of fat pad PDW-SPAIR were analyzed to evaluate their application value in patients with KOA.ResultsAmong the 82 patients, there were 25 cases of bony defects, 43 cases of cartilage defects, and 14 cases of hydrops articuli. There were 63 cases of bone marrow edema, 54 cases of soft tissue swelling, 68 cases of synovitis, and 42 cases of bone erosion. Different quantitative parameters of fat pad PDW-SPAIR showed that patients with cartilage defects were 50, 53, 32, and 32. Cartilage defects were 130, 131, 53, and 49. There were statistically significant differences in signal intensity ratios of non-cartilage and cartilage defects displayed by different quantitative parameters of fat pad PDW-SPAIR (p < 0.05). Spearman correlation analysis showed that PD-FSE-SAG-SPAIR, PD-FSE-COR-SPAIR, T2-FSE-SAG, and T1-FSE-COR positively correlated with KOA (p < 0.05).ConclusionMRI manifestations and quantitative parameters of fat pad PDW-SPAIR may be helpful for the clinical prediction of KOA.